Sustained censorship in TR (2026-06) (Turkey) - Voidly (Voidly Global Censorship Index, 2026)
WARNING severity censorship detected in Turkey. Data sourced from OONI.
Censorship Incident ID: TR-2026-0134. Severity: warning. Confidence: 75%